THE SITUATION AND EFFECTS OF CLIMATE CHANGE AND AIR POLLUTION - Szűcs, Csaba (Acta Carolus Robertus, 2021)
Global climate change poses a serious threat to the inhabitants of the Earth. Reducing human impacts on the Earth’s climate is necessary to minimize the adverse consequences of extreme weather events. Accordingly, there is an urgent need to develop action plans at global, regional and national levels. The United Nations Intergovernmental Panel on Climate Change (IPCC) confirms the fact that human activity is behind the rise in global average temperatures. The report explains that increasing GHG emissions cause changes in the oceans, affect polar ice caps as well as the biosphere and other elements of the climate system. Global climate change must be mitigated by all means. In the course of my work I study air pollutant emissions in Hungary and present the trends of changes in the main indicators.
Keywords: climate change; sustainability; indicators; energy production; carbon dioxide emissions